Longitudinal changes in sensory impairments and subsequent falls and fall-related injuries among middle-aged and older adults: a pooled analysis of four prospective cohorts - De Moraes-Ferrari, G (BMC, 2025)
BackgroundVisual and hearing impairments are recognized as modifiable risk factors for falls. However, evidence on the longitudinal effects of changes in sensory status on the risk of falls and fall-related injuries remains limited. This study aimed to examine the association between changes in sensory impairment status and the incidence of falls and fall-related injuries among middle-aged and older adults.MethodsSelf-reported visual and hearing impairments were assessed at baseline and at a follow-up survey conducted two to three years later. The primary outcomes were incident falls and fall-related injuries. Modified Poisson regression models with robust standard errors were used to estimate risk ratios (RRs) and 95% confidence intervals (CIs).ResultsA total of 22,287 participants were included in the main analysis. Compared with maintaining good sensory function, new-onset sensory impairments, recovery from sensory impairments, and persistent sensory impairments were associated with higher risks of falls and fall-related injuries. New-onset sensory impairments were associated with a 20% higher risk of falls (RR = 1.20, 95% CI: 1.13-1.26) and a 37% higher risk of fall-related injuries (RR = 1.37, 95% CI: 1.22-1.54). Recovery from sensory impairments was associated with a modestly increased risk of falls (RR = 1.08, 95% CI: 1.02-1.15) and fall-related injuries (RR = 1.21, 95% CI: 1.07-1.38), while persistent sensory impairments were associated with the highest risks (falls: RR = 1.24, 95% CI: 1.18-1.29; fall-related injuries: RR = 1.45, 95% CI: 1.32-1.60). When compared with persistent sensory impairments, recovery was associated with a significantly lower risk of falls (RR = 0.88, 95% CI: 0.83-0.93) and fall-related injuries (RR = 0.83, 95% CI: 0.74-0.94).ConclusionsLongitudinal changes in sensory impairments are strongly associated with the risk of falls and fall-related injuries. Recovery from sensory impairment appears to be linked to a reduced risk, underscoring the potential benefits of interventions aimed at restoring sensory function.